2012
DOI: 10.1302/0301-620x.94b9.28881
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of combined unicompartmental knee replacement and combined or sequential anterior cruciate ligament reconstruction

Abstract: The Oxford unicompartmental knee replacement (UKR) is an established treatment option in the management of symptomatic end-stage medial compartmental osteoarthritis (MCOA), which works well in the young and active patient. However, previous studies have shown that it is reliable only in the presence of a functionally intact anterior cruciate ligament (ACL). This review reports the outcomes, at a mean of five years and a maximum of ten years, of 52 consecutive patients with a mean age of 51 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 31 publications
1
73
0
7
Order By: Relevance
“…Treatment with HTO ACL reconstruction had the lowest revision rate (0.62/100 observed component years) but the highest rate of complications (4.61/100 observed component years). Too little data were available to test for differences in In this latter group with ACL deficiency secondary to OA, a total knee arthroplasty (TKA) is considered the treatment of choice [34,37,44]; however, there is no consensus on the treatment of medial knee OA in ACL deficiency patients where ACL deficiency is the primary pathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with HTO ACL reconstruction had the lowest revision rate (0.62/100 observed component years) but the highest rate of complications (4.61/100 observed component years). Too little data were available to test for differences in In this latter group with ACL deficiency secondary to OA, a total knee arthroplasty (TKA) is considered the treatment of choice [34,37,44]; however, there is no consensus on the treatment of medial knee OA in ACL deficiency patients where ACL deficiency is the primary pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Due to younger age and higher activity levels seen in patients with primary ACL deficiency who develop secondary OA, bone conserving options are preferred with TKA not being recommended as the primary treatment option in this cohort [37,44]. At the other end of the spectrum ACL reconstruction alone, with the exception of those patient who report instability as their primary complaint, is not a definitive treatment option but can be used as a reasonable, low co-morbidity treatment option to improve symptoms prior to subsequent HTO or UKA [47].…”
Section: Introductionmentioning
confidence: 99%
“…Pandit et al 52 and Weston-Simon et al 53 suggest taking a different surgical approach according to the predominant symptom. When pain is the main symptom, simultaneous ACL reconstruction and mobile UKA are indicated to ensure the best outcome; when joint instability is the main complaint, ACL reconstruction is the primary procedure.…”
Section: Patient Selection and Preoperative Evaluationmentioning
confidence: 99%
“…More latterly, medial UKRs have been performed in conjunction with an ACL reconstruction with good survivorship and outcome scores. 16 Mobile or fixed bearing device In an attempt to minimise wear, some fixed bearing components were introduced that had increased conformity, compared to the classic round-on-flat articulation. When failed non-conforming implants were studied, they found that the prosthetic articulation has a propensity to replicate that of the pre-operative arthritic wear pattern, which tends to be peripheral and anterior in the varus knee.…”
Section: Indications For Ukrmentioning
confidence: 99%
“…They found that the rate of revision of a TKA done following a UKR was four times that of a primary TKA; they also found a significantly worse Oxford knee score in the conversion group as compared to the primary group (30.02 vs 37. 16) This would indicate that a revision of a UKR to a TKA should be viewed more like a full revision procedure rather than a conversion to a conventional primary. 22 This does, however, contrast with the findings of the Oxford knee group who found the conversion of a UKR to a TKA gives equivalent outcomes to a primary TKA.…”
Section: Age and Ukrmentioning
confidence: 99%